Adaptation Difficulties of Students with Hearing Impairments - Yadavalli, Dr. Pavan Kumar (International Journal of Psychosocial Rehabilitation, 2010)
The present study aims at investigating the adaptation difficulties of hearing-impaired students studying in X class in special schools with regard to their gender differences and level of severity of hearing impairment. To identify the gender differences in the adaptation difficulties of hearing-impaired students and to find out the differences in the level of severity of hearing impairment on the adaptation difficulties of hearing-impaired students. 262 boys and 172 girls with hearing impairments were selected, respectively, from different special schools in Andhra Pradesh. 256 students with profound hearing impairments, 137 students with severe hearing impairments, and 41 students with moderate hearing impairments were selected for the present study. Based on the findings, it can be concluded that in general, the 10th class students have less adaptation difficulties. Type of defect showed a significant influence on the overall adaptation difficulties and also different areas of adaptation difficulties. Based on the statistical analysis, the type of defect showed a significant influence on the overall adaptation difficulties and also different areas of adjustment challenges.